The Spring Queen pageant and the postapartheid archive. Issue 2 (3rd April 2017) - O'Connell, Siona
Abstract: This paper considers how an archive of the "Spring Queen" pageant of clothing and textile workers of the Cape Flats of Cape Town can be examined for insights into the past and present lives of those oppressed by apartheid. It considers further the idea of the ordinary archive and peripheral narratives as entrypoints into how we may yet understand self-representation and freedom in post-apartheid South Africa.